Metastatic Leiomyosarcoma to the Spine Complicated With Thrombocytopenia - Shirzadi, Ali (World J Oncol, 2012)
Uterine leiomyosarcomas do not frequently metastasize to the bone, and spinal column metastases are even less common. Surgery is the treatment of choice. Adjuvant radiation with or without chemotherapy depending on the extent of disease can be beneficial. We present the case of leiomyosarcoma metastasis to the spine with a previous history of known primary disease complicated by thrombocytopenia. Thrombocytopenia can present surgical challenges, but can also be present concurrently unrelated to the primary disease. A thorough evaluation is needed to rule out any underlying lymphoproliferative disorder or microangiopathic phenomenon.